Acylamino acid chiral fungicides on toxiciepigenetics in lambda DNA methylation. (November 2017) - Yin, Jing; Zhu, Feilong; Hao, Weiyu; Xu, Qi; Chang, Jin; Wang, Huili; Guo, Baoyuan
Abstract: Acylamino acid chiral fungicides (AACFs) are low-toxicity pesticides and considered as non-carcinogenic chemicals to laboratory animals. Though AACFs have potential toxicological effects on mammals by non-genotoxic mechanisms, the toxicoepigenomics of AACFs has not been documented. In this article, we explored toxiciepigenetics of metalaxyl, benalaxyl and furalaxyl through epigenetics research on lambda DNA under different concentration exposure. The toxicoepigenomic difference of stereoisomers was examined also. Our results showed that AACFs would affect methyltransferase activity resulting in modulating DNA methylation levels and pattern. The LOAEL of R-metalaxyl and S-metalaxyl were 30 mM and 0.3 mM, respectively. The LOAEL of (R, S)-benalaxyl and (R, S)-furalaxyl were 0.3 Mm and 30 mM, respectively. A significant dose-response effect between (R, S)-benalaxyl and global methylation level was observed. Global methylation level was more susceptible to S-enantiomer compared to R-enantiomer, which indicated enantiomers of AACFs have the enantioselectivity in toxiciepigenetics. Moreover, the dependence of the methylation inhibition on the chiral center of metalaxyl may suggest a considerable specificity of the compound of AACFs for DNA methyltransferases. The inhibition effect between R-enantiomer and S-enantiomer of AACFs on DNA methylation levels generated in this study is important for low-toxicity pesticides toxicoepigenomics evaluation. Graphical abstract: Highlights: Lambda DNA methylation levels and pattern were changed under AACFs exposure. The difference in toxiciepigenetics may be caused by the structure of AACFs. Enantiomers of AACFs have the enantioselectivity in toxiciepigenetics. Chiral center has specificity for methyltransferases. Low toxicity pesticides may have toxicoepigenomics.